2020
DOI: 10.2118/199266-pa
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach to Well Productivity Evaluation To Determine the Significance of Formation Damage for Wells Drilled in a Depleted Reservoir without Bridging Particles: Oseberg Main Case History

Abstract: Summary As part of an Equinor technical efficiency program that was initiated in 2015 to deliver savings and improvements, bridging particles were removed from the drilling fluids of 15 wells in Oseberg Main and instead loss control material (LCM) was used, as required, in some but not all the wells. These long, horizontal wells were a combination of open hole (OH) and sand screens with and without inflow control together with cased and perforated (C&P) completions, producing from typical Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Contrary to the report of Vickers et al [90], Fleming [97] carried out a field study on the importance of damage reaction for 15 oil wells completed in a low-pressure sandstone production zone located in the Oseberg Formation, Norway, without bridging particles. Fleming [97] observed that the use of drilling fluids formulated without sealing materials for these 15 wells in the Oseberg Formation led to unanticipated results, with the absence of formation damage reactions due to filtration loss in the 15 completed oil wells Fleming [97] concluded that the Brent reservoir sections in the Oseberg Formation were unsusceptible to damage reaction due to filtration loss, despite being depleted [97].…”
Section: Mitigating Formation Damage Through the Design And Selection Of Drilling Fluidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Contrary to the report of Vickers et al [90], Fleming [97] carried out a field study on the importance of damage reaction for 15 oil wells completed in a low-pressure sandstone production zone located in the Oseberg Formation, Norway, without bridging particles. Fleming [97] observed that the use of drilling fluids formulated without sealing materials for these 15 wells in the Oseberg Formation led to unanticipated results, with the absence of formation damage reactions due to filtration loss in the 15 completed oil wells Fleming [97] concluded that the Brent reservoir sections in the Oseberg Formation were unsusceptible to damage reaction due to filtration loss, despite being depleted [97].…”
Section: Mitigating Formation Damage Through the Design And Selection Of Drilling Fluidsmentioning
confidence: 97%
“…Between 1992 and 2020, drilling fluids that are not laden with solids have gained increased prominence in the industry as FDM/FDC measures for damage reaction due to invading particles, and many researchers (e.g., [12,[97][98][99]) have presented their opinions concerning the use of drilling fluids with few or no additives for use as RDFs. However, it is equally significant to manage anticipated formation damage challenges in reservoirs with varying clay minerals, because individual clay mineral species interact with drilling fluids of varying formulations in a variety of ways, giving rise to filter cakes of varying permeability and thickness.…”
Section: Mitigating Formation Damage Through the Design And Selection Of Drilling Fluidsmentioning
confidence: 99%